Development of Circular Drug Delivery Device for the Treatment of Fungal Keratitis - Magazov, Yerbolat (Nazarbayev University School of Engineering and Digital Sciences, 2020)
Fungal keratitis is a dangerous infectious eye disease in which the cornea becomes inflamed and swollen, which can cause pain and redness of the eye, and without proper treatment, it can lead to loss of vision. Despite the widespread use of anti-fungal drugs, the only available forms are tablets and liquid suspensions, so the drug can only be taken orally, intravenously or in the form of eye drops. However, due to the significant drawbacks like poor biocompatibility, a short period of activity and low permeability of the intraocular drug, it is necessary to develop an alternative method that allows delivering the drug of choice to the damaged areas effectively. This work presents the possibility of creating a drug delivery device in the form of a hydrogel ring that is capable of treating keratitis effectively. In this study, voriconazole was chosen as the antifungal drug as it is a better option in comparison with traditional antifungal agents since it showed a promising result in the treatment of yeast and filamentous fungi. Regarding the circular drug delivery device, unique hydrogel rings have been developed to have the property to swell when the drug is introduced into them. Thus, the rings hold the required amount of the drug when in contact with voriconazole while maintaining its shape. A filled ring is inserted into the eye and releases voriconazole while providing a more local and effective treatment for keratitis in a short period. In this case, patients will not have to use eye drops so often; instead, they only need to wear these devices, and during the day, the medicine will slowly release, providing an antifungal effect with enhanced bioavailability. The biggest objective of this work was to show that a particular drug delivery device can provide drug concentration at a therapeutic level for long-duration, excluding the frequent application the eye drops. XPS and SEM-EDS analysis demonstrated that our synthesized hydrogel rings indeed consist of PVP, and voriconazole loading into the hydrogel structure was successful. In addition, the porosimetry test verified that hydrogel rings have pores with diameters 5-25 nm (54%) and 7-240 μm (46%), and a porosity of 30% provides enough space for penetration and precipitation of voriconazole crystals in the pores of the polymer rings. The drug release experiments showed that voriconazole released from the device during the two days, and after the concentration of voriconazole in PBS solution were maintained at 80 μg/mL. Another performed release study, where hydrogel rings were subjected to a new PBS solution environment, demonstrated that it could release the drug for at least ten days.
Keywords: Dimethyl sulfoxide; Deoxyribonucleic acid; Energy-dispersive X-ray spectroscopy; Food and Drug Administration; 1,6-Hexanediol dimethacrylate; HDDMA; Absorbance; Porosity; Research Subject Categories::TECHNOLOGY